The Role of Race and Gender in Nutrition Habits and Self-Efficacy: Results from the Young Adult Weight Loss Study - Janna D. Stephens; Andrew Althouse; Alai Tan; Bernadette Mazurek Melnyk (Hindawi Limited, 2017)
Overweight and obesity are a massive public health problem and young adults are at high risk for gaining weight once they enter a college. This study sought to examine gender and race as they relate to nutrition habits and self-efficacy in a population of diverse young adults from the Young Adult Weight Loss Study. Participants (N=62) were 29% males, 38.7% white, 33.8% Asian, and 12.9% African American. Males had lower self-efficacy for healthy eating (mean score = 92.5, SD = 17.1) compared to females (mean = 102.3, SD = 13.7, p=0.02). Males had higher consumption of sodium compared to females (4308 versus 3239 milligrams/day, p=0.01). There were no significant differences across racial subgroups in self-efficacy for healthy eating (p=0.67) or self-efficacy for exercise (p=0.61). Higher self-efficacy scores for healthy eating were significantly associated with less total sodium (r=-0.37, p=0.007), greater fruit consumption, and less saturated fat. Our results indicate that weight loss interventions should be individualized and that there may be specific areas to target that are different for men and women. Additional larger studies should be conducted to confirm if racial differences exist across nutrition habits and self-efficacy and to confirm gender differences noted in this study.